2021
DOI: 10.1159/000520280
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Melatonin and Insulin Improves Diabetes-Induced Impairment of Rat Kidney Function

Abstract: Introduction: The present study was designed to evaluate the therapeutic efficacy of melatonin and insulin co-administration in diabetic-induced renal injury in rats. Research design and methods: Diabetes was achieved by giving streptozotocin (15 mg/kg) for 6 consecutive days and animals having blood glucose levels above 250mg were considered as diabetic. Following the confirmation, animals were randomly divided into different experimental groups, viz group-I, group-II, group-III, group IV, group V, group VI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…A large number of literature suggest a correlation between disturbed sleep orders and decreased glucose tolerance and T2D (Donga et al 2010 ; Yaggi et al 2006 ). A study reported by Hajam et al ( 2022 ) has reported the therapeutic efficacy of coadministration of insulin and melatonin rat models with diabetes-induced renal injury. The outcome of the study reported has revealed that the combination of insulin and melatonin may be quite effective to treat renal alterations caused by diabetes as confirmed by sera biochemical parameters, anti-inflammatory molecules in serum, and histoarchitecture changes in kidney (Hajam et al 2022 ).…”
Section: Melatonin and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of literature suggest a correlation between disturbed sleep orders and decreased glucose tolerance and T2D (Donga et al 2010 ; Yaggi et al 2006 ). A study reported by Hajam et al ( 2022 ) has reported the therapeutic efficacy of coadministration of insulin and melatonin rat models with diabetes-induced renal injury. The outcome of the study reported has revealed that the combination of insulin and melatonin may be quite effective to treat renal alterations caused by diabetes as confirmed by sera biochemical parameters, anti-inflammatory molecules in serum, and histoarchitecture changes in kidney (Hajam et al 2022 ).…”
Section: Melatonin and Diabetesmentioning
confidence: 99%
“…A study reported by Hajam et al ( 2022 ) has reported the therapeutic efficacy of coadministration of insulin and melatonin rat models with diabetes-induced renal injury. The outcome of the study reported has revealed that the combination of insulin and melatonin may be quite effective to treat renal alterations caused by diabetes as confirmed by sera biochemical parameters, anti-inflammatory molecules in serum, and histoarchitecture changes in kidney (Hajam et al 2022 ). The melatonin administration modulates the synthesis of insulin in the pancreatic β-cells as well as enhancing the optimistic insulin effect (Hajam and Rai 2019 ).…”
Section: Melatonin and Diabetesmentioning
confidence: 99%
“…A plethora of preclinical studies indicate the utility of melatonin in attenuating many of the consequences of T1DM, including the following: cardiovascular disorders [ 181 ], pancreatic β-cell regeneration [ 109 ], renal impairment [ 182 ], bone loss [ 183 ], cognitive deficits [ 110 ], erectile dysfunction [ 184 ], and body temperature circadian rhythm [ 185 ]. This is supported by clinical data showing lower melatonin levels in T1DM children [ 186 ].…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Transforming growth factor-β1-treated NRK-49F cells treated with MT exhibited lower levels of intracellular ROS and malondialdehyde, as well as ameliorated reductions of the glutathione/oxidized glutathione ratio [ 128 ]. Moreover, the addition of MT treatment in diabetic Wistar rats receiving insulin resulted in downregulated expression of GSH, GSH reductase, glucose-6-phosphate dehydrogenase, and GSH-S-transferase in the renal cortex [ 129 ]. MT also improved DN in albino rats by suppressing renal malondialdehyde and stimulating antioxidant systems such as GSH, SOD, and catalase [ 116 ].…”
Section: Antioxidant Pharmacotherapies In Cardiorenal Diseasesmentioning
confidence: 99%